2015
DOI: 10.17140/semoj-1-116
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of Critical Power, The Onset of Blood Lactate and Anaerobic Capacity for Cross-Country Mountain Bike Race Performance

Abstract: CitationMiller MC, Macdermid PW. Predictive validity of critical power, the onset of blood lactate and anaerobic capacity for cross-country mountain bike race performance. Case ReportPage 105 ABSTRACTCritical power is emerging as an important indicator of high intensity endurance exercise capability. Little is known regarding its ability to predict performance during high intensity intermittent events such as Olympic format cross country mountain bike racing. Therefore, the purpose of this pilot study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Several studies have shown the importance of aerobic characteristics for performance, such as maximal oxygen uptake (V̇O 2max ; Impellizzeri and Marcora, 2007 ; Hays et al, 2018 ), maximal aerobic power (MAP) output ( Granier et al, 2018 ; Hays et al, 2018 ), and ventilatory and lactate thresholds ( Impellizzeri et al, 2005a ; Miller et al, 2014 ; Miller and Macdermid, 2015 ; Viana et al, 2018 ). Anaerobic power has also been classified as an important determinant of performance because of the intermittent aspect of XCO racing ( Inoue et al, 2012 ), but to date, there have been limited studies conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the importance of aerobic characteristics for performance, such as maximal oxygen uptake (V̇O 2max ; Impellizzeri and Marcora, 2007 ; Hays et al, 2018 ), maximal aerobic power (MAP) output ( Granier et al, 2018 ; Hays et al, 2018 ), and ventilatory and lactate thresholds ( Impellizzeri et al, 2005a ; Miller et al, 2014 ; Miller and Macdermid, 2015 ; Viana et al, 2018 ). Anaerobic power has also been classified as an important determinant of performance because of the intermittent aspect of XCO racing ( Inoue et al, 2012 ), but to date, there have been limited studies conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, laboratory tests of aerobic fitness are not readily available to coaches and athletes due to the need for advanced equipment. Noticing the lack of an ecological testing method, Miller and Macdermid (2015) proposed critical power (CP) as an ecological framework to assess performance in XCO. CP is considered to be the highest sustainable rate of oxidative metabolism without a continuous loss of homeostasis, defined as the boundary between steady state and non-steady state exercise ( Poole et al, 1988 ; Jones et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%